Experience in the treatment of patients with androgenic deficiency and comorbidity pathology - Arsen V. Osipov; Tatyana I. Derevyanko; Nadezhda V. Agranovich; Roman S. Frantsev; Gayane H. Babasheva; Olga A. Alexandrova (ZAO "Consilium Medicum", 2024)
Background. Age-related involution of the male reproductive system, known as testosterone deficiency syndrome, andropause, androgen deficiency in the aging male, or partial androgen deficiency in the aging male, causes clinical manifestations that impair quality of life and increase the risk of mortality, especially from cardiovascular disease. In Russia, the problem of hypodiagnosis of androgen deficiency remains up-to-date, with a low frequency of prescription of replacement therapy. Aim. At assessing the effectiveness of testosterone in the rehabilitation of patients with hypogonadism and cardiovascular pathology. Materials and methods. It involved 36 men aged 25-75 years with various cardiological pathologies. Results. As a result of the study, testosterone as a form of a transdermal gel is effective at doses of 50 mg/day. Three-month use of testosterone gel increases the level of testosterone to 2.9 nmol/l (p0.05). Conclusion. Thus, testosterone may play a key role in the treatment of hypogonadism and related cardiovascular diseases, although its safety and feasibility remain a matter of debate.